Imaging local electrochemical current via surface plasmon resonance - Shan, Xiaonan (2010)
We demonstrated an electrochemical microscopy technique based on the detection of variations in local electrochemical current from optical signals arising from surface plasmon resonance. It enables local electrochemical measurements (such as voltammetry and amperometry) with high spatial resolution and sensitivity, because the signal varies with current density rather than current. The imaging technique is noninvasive, scanning-free, and fast, and it constitutes a powerful tool for studying heterogeneous surface reactions and for analyzing trace chemicals.